Znaczenie „ościenia dla ciała” (2 Kor 12,7-10) w retoryce św. Pawła - Chwiła, Dorota (Warszawskie Studia Teologiczne, 2021)
St Paul uses the phrase ’a thorn in the flesh’ in the Second Epistle to the Corinthians (2 Cor 12:7). Over the centuries, this metaphor has received many different interpretations. Three main categories in these interpretations seem to stand out. The first one understands the mentioned metaphor as a physical ailment. The second one as the experience of temptation and in the third category, are those who were against Paul and who caused him much pain and suffering. A rhetorical analysis of Paul’s speech, contained in 2 Corinthians 10-13, shows the right identification of "a thorn in the flesh" with those who oppose him. The main argument of the discourse, confirms the proclamation, that the apostolate of Paul is Christ’s and he himself belongs to Christ. His opponents are false apostles who cause Paul to suffer much.